2016
DOI: 10.1128/mbio.00808-16
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Biotinylation of the Toxoplasma Parasitophorous Vacuole Reveals Novel Dense Granule Proteins Important for Parasite Growth and Pathogenesis

Abstract: Toxoplasma gondii is an obligate intracellular parasite that invades host cells and replicates within a unique parasitophorous vacuole. To maintain this intracellular niche, the parasite secretes an array of dense granule proteins (GRAs) into the nascent parasitophorous vacuole. These GRAs are believed to play key roles in vacuolar remodeling, nutrient uptake, and immune evasion while the parasite is replicating within the host cell. Despite the central role of GRAs in the Toxoplasma life cycle, only a subset … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
146
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(159 citation statements)
references
References 66 publications
9
146
0
2
Order By: Relevance
“…In contrast to microneme and rhoptry genes, there were 25 genes out of the 48 annotated and/or reported to encode dense granule and dense granule-like proteins (ToxoDB, [33]) that had higher expressions in intracellular sporozoites compared to tachyzoites (Table 10). Interestingly, these include genes for the recently characterized GRA24, GRA16, GRA28, and GRA31 [33,60,61].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast to microneme and rhoptry genes, there were 25 genes out of the 48 annotated and/or reported to encode dense granule and dense granule-like proteins (ToxoDB, [33]) that had higher expressions in intracellular sporozoites compared to tachyzoites (Table 10). Interestingly, these include genes for the recently characterized GRA24, GRA16, GRA28, and GRA31 [33,60,61].…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, these include genes for the recently characterized GRA24, GRA16, GRA28, and GRA31 [33,60,61]. Notably, GRA28 had the highest level of differential expression between the sporozoites and tachyzoites, with 12.5-fold higher expression in sporozoites than in tachyzoites ( q -value = 0.77% at FDR 10%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…15 Previously, we reported that T. gondii infection suppressed apoptosis of HeLa cells for 36hours post-infection in uninfected cells and in cells treated with actinomycin D. 16 T. gondii uses a mixture of specialized parasite secreted proteins, including ROPs, GRAs and MICs to invade cells. 17,18 Many of these parasite secreted proteins are anchored on the parasitophorous vacuole membrane (PVM) and can interact with the host cells directly. The kinase activity ROPs, such as ROP2, 19 …”
Section: Discussionmentioning
confidence: 99%
“…(2015) adapted BioID for use in T. gondii , identifying several novel protein components of the inner membrane complex (IMC). BioID has since been employed in T. gondii research to identify interactors of kinases (Gaji et al ., 2015), calmodulins (Long et al ., 2017a), and to define the protein repertoire of other cellular compartments including the parasitophorous vacuole (Nadipuram et al ., 2016), sutures of the IMC (Chen et al ., 2017), and the apical complex (Long et al ., 2017b). Here we will describe the protocol for generating a BirA gene fusions using CRISPR/Cas9 tagging (Shen et al ., 2014; Shen et al ., 2017), in vivo BirA biotin labeling and purification of biotinylated proteins from parasites, and identification of captured biotinylated proteins by mass-spectrometry.…”
Section: [Background]mentioning
confidence: 99%